Diet and genotype effects on the quality index of beef produced in the Argentine Pampeana region - Latimori, Nestor Juan (2008)
Steers of varying genotypes (Aberdeen Angus, Charolais x AA and Argentine Holstein) in four feeding systems were evaluated. Feeding systems were: S1 = a diet based on pastures only; S2 = a similar forage base as S1 plus a daily supplementation with cracked corn, at 0.7% of l.w./head/day; S3 = a similar forage base as S1 plus a daily supplementation with cracked corn, at 1.0% of l.w./head/day; and S4 = a regular feedlot diet. Tenderness and marbling were not affected by the feeding system. Feedlot meat showed an n-6/n-3 ratio significantly higher than meat produced with the diets based on pastures (S1 = 2.1; S2 = 3.1; S3 = 4.5; S4 = 14.2) (P < 0.05), whereas CLA content had an inverse behavior, showing S1 (0.67%) and S2 (0.64%) higher concentrations than S3 (0.55%) and S4 (0.28%) (P < 0.05). Diet based on pastures plus a low level of supplementation produced meat with better nutritional characteristics than other productive alternatives, without significant effects of the biotypes.